Plant associated protists—Untapped promising candidates for agrifood tools. (12th December 2022) - Nguyen, Bao‐Anh Thi; Dumack, Kenneth; Trivedi, Pankaj; Islam, Zahra; Hu, Hang‐Wei
Abstract: The importance of host‐associated microorganisms and their biotic interactions for plant health and performance has been increasingly acknowledged. Protists, main predators and regulators of bacteria and fungi, are abundant and ubiquitous eukaryotes in terrestrial ecosystems. Protists are considered to benefit plant health and performance, but the community structure and functions of plant‐associated protists remain surprisingly underexplored. Harnessing plant‐associated protists and other microbes can potentially enhance plant health and productivity and sustain healthy food and agriculture systems. In this review, we summarize the knowledge of multifunctionality of protists and their interactions with other microbes in plant hosts, and propose a future framework to study plant‐associated protists and utilize protists as agrifood tools for benefiting agricultural production.